Microbial Isolation - Rhezqy Furwati Jufri (Journal La Lifesci, 2020)
The importance of isolating a microbe from the environment, such as food (solid substrate), drinks (liquid substrate), and yourself because of the many microbes that are difficult to observe or distinguish directly using the five senses. A sample can contain bacteria or fungi. By isolating, the shape of the colonies and the contents in a sample can be observed. Bacteria from the air and normal flora form colonies with lobate-shaped edges, whereas bacteria found in well water samples form colonies with irregular edges and there are also fungi found in the well water samples.